Ticks and Tularemia: Do We Know What We Don't Know? - Zellner, Briana; Huntley, Jason F. (Frontiers in Cellular and Infection Microbiology, 2019)
Francisella tularensis, the causative agent of the zoonotic disease tularemia, is characterized by high morbidity and mortality rates in over 190 different mammalian species, including humans. Based on its low infectious dose, multiple routes of infection, and ability to induce rapid and lethal disease, F. tularensis has been recognized as a severe public health threat—being designated as a NIH Category A Priority Pathogen and a CDC Tier 1 Select Agent. Despite concerns over its use as a bioweapon, most U.S. tularemia cases are tick-mediated and ticks are believed to be the major environmental reservoir for F. tularensis in the U.S. The American dog tick (Dermacentor variabilis) has been reported to be the primary tick vector for F. tularensis, but the lone star tick (Amblyomma americanum) and other tick species also have been shown to harbor F. tularensis. This review highlights what is known, not known, and is debated, about the roles of different tick species as environmental reservoirs and transmission vectors for a variety of F. tularensis genotypes/strains.